Gaps and opportunities in mental health support for young people: a process evaluation of a multi component intervention - Oha, Jessica T.; Bridge, Gemma; Flood, Chris; Jenkins, Catherine L.; Taylor-Page, Charlotte; Sykes, Susie; Wills, Jane; York, Wendy; Callaghan, Patrick; Reavey, Paula (Frontiers in Public Health, 2025)
BackgroundYoung people aged 16–25 are reporting rising rates of poor mental health, exacerbated by service gaps. Key life transitions such as moving from school to college, or into the workforce can increase vulnerability.MethodA mixed-methods evaluation was conducted of a multi-component, mental health intervention in the East of England. The evaluation aimed to: (1) Assess the fidelity, dose, and reach of the intervention; (2) Understand the mechanisms of impact and how change was generated; (3) Explore the influence of context, including dynamic relationships between those involved in delivering and accepting support, settings, and service delivery models; and (4) Assess if the intervention offered good value for money. Semi-structured interviews were held with local public health staff (n = 3), and an intervention lead. A focus group was conducted with intervention leads (n = 3). Photo production interviews were held with young people (n = 10). Quantitative outcomes were explored through pre- and post- questionnaires (n = 34), and pre-post intervention assessment of young people’s wellbeing, and satisfaction with the intervention, using the DIALOG (n = 34) and Wellbeing star measures (n = 37). Value for money was assessed using commissioned, in-house cost data and qualitative insights.ResultsThe intervention demonstrated positive outcomes in life satisfaction and functional wellbeing for young people, with young people engaging across the intervention components (n = 82, CC Hubs, n = 74, WN, n = 53, BR). The most cost-effective components were Upskilling the Workforce and Wellbeing Navigator support. Third spaces, and creative methods, fostered engagement and acceptability among young people.ConclusionIntegrated, co-produced, and place-based approaches can support young people’s mental health needs during life transitions. Investment in local partnerships and youth-centred design is important.